Utilização do AutoCAD 2004 para quantificação de pesquisas usando fotomicrografias eletrônicas - Almeida, Carla Albertina Martins [UNESP]; Schellini, Silvana Artioli [UNESP]; Gregório, Elisa Aparecida [UNESP]; Pellizzon, Claudia Helena [UNESP] (Revista Brasileira de Oftalmologia, 2007)
Objective: To determine if the AutoCAD 2004 program is available to be used in quantitative research on electron microscopy. Methods: A demonstrative of the AutoCAD2004 was done in an experimental model of diabetes induced in rats. The animals were divided by lot in control group animals (GC-10 animals) and diabetic group (GD - 10 animals), evaluated 1 month after the diabetes induction.The eyes were removed after sacrifice and prepared to electron microscopy. The retina was photographed and the AutoCAD2004 program was used to measure the basal membrane of retina vessels. The results were submitted to statistical analysis. Results:The AutoCAD2004 was effective to obtain quantitative measures from the basal membrane of retina vessels and there were no difference between the studied groups. Conclusion: The AutoCAD2004 was effective, safe and easy to apply to quantify biological parameters, which allowed suggest it to quantitative research.
AutoCAD 2004 to quantify electron-photomicrography
Keywords: Microscopy, electron/methods; Retinal vessels; Software